The Interplay of Psychological Stressors and Team Dynamics: Evaluating Competition Anxiety and Aggression in Relation to Physical Performance and Health - Mukhtar Ahmad Wani; Vikas Saxena (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This research explores the complex relationship between psychological stressors particularly competition anxiety and aggression and their influence on team dynamics, physical performance, and overall health in ball game players. Drawing on quantitative and qualitative data collected from athletes engaged in team sports such as football, basketball, and volleyball, the study investigates how stress and behavioral factors shape athletic performance and interpersonal cohesion. Findings reveal significant correlations between heightened anxiety and decreased performance, while group cohesion emerged as a moderating factor. The paper concludes with strategies for coaches and sports psychologists to manage psychological stressors to enhance both physical outcomes and mental well-being.